1979
DOI: 10.1677/joe.0.0800343
|View full text |Cite
|
Sign up to set email alerts
|

Mammary Growth During Pregnancy in Hypophysectomized or Bromocriptine-Treated Goats

Abstract: Mammogenesis in primiparous hypophysectomized goats has been assessed between days 60 and 120 of gestation and compared with that found in untreated goats and goats treated with 5 mg bromocriptine/day. There were fivefold increases in the weight of lobulo-alveolar tissue in the hypophysectomized and bromocriptine-treated goats and a tenfold increase in the untreated goats. Histological examination of the mammary glands at 120 days showed normal structure, and determinations of lactose, lactose synthetase, cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

1980
1980
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 30 publications
2
24
1
Order By: Relevance
“…In this connection, there is substantial evidence that placental lactogen is an important hormone in sheep (Martal andDjiane 1975, 1977;Kelly et al 1976) and goats (Kelly et al 1976; Buttle et al 1979). It is pertinent that the blood concentration of prolactin of pregnant sheep, goats and cows is low until shortly before parturition (Johke et al 1971;Fell et al 1972;Lamming et al 1974).…”
Section: Discussionmentioning
confidence: 99%
“…In this connection, there is substantial evidence that placental lactogen is an important hormone in sheep (Martal andDjiane 1975, 1977;Kelly et al 1976) and goats (Kelly et al 1976; Buttle et al 1979). It is pertinent that the blood concentration of prolactin of pregnant sheep, goats and cows is low until shortly before parturition (Johke et al 1971;Fell et al 1972;Lamming et al 1974).…”
Section: Discussionmentioning
confidence: 99%
“…Relaxin synergizes with pituitary and ovarian hormones to stimulate growth in young ovariectomized-hypophysectomized rats (Harness & Anderson, 1977) but inhibits steroidinduced mammary development in virgin goats (Cowie et al, 1965) Anderson, 1975a) or only partly inhibited (e.g. goats: Buttle, Cowie, Jones & Turvey, 1979; sheep: Denamur & Martinet, 1961). Ovariectomy or fetectomy of pregnant rats and mice has no significant effect on mammogenesis, either, provided that the placentae remain intact; if the placentae are removed then mammogenesis ceases (Desjardins, Paape & Tucker, 1968).…”
Section: Systemic Endocrine Controlmentioning
confidence: 99%
“…Several studies have shown that this PRL pulse is also essential for the initiation of lactation. Treatment at the end of pregnancy with the dopamine agonist bromocriptine (BRO) to suppress the peripartum PRL pulse results in a complete failure of milk production and the subsequent death of the neonates (Buttle et al 1979, Fletcher et al 1990. One of the possible mechanisms of this crucial PRL effect is the well-documented dependence of cyclin D1 synthesis in the mammary gland on PRL (Brockman et al 2002).…”
Section: Introductionmentioning
confidence: 99%